"If the coronavirus doesn't kill us, hunger will": Regional absenteeism and the Wayuu permanent humanitarian crisis. Issue 3 (1st December 2020) - Puerta Silva, Claudia; Torres Muriel, Esteban; Amaya Epiayú, Roberto Carlos; Dorado González, Alicia; Epieyú, Fatima; Frías Epinayú, Estefanía; Ipuana Guariyü, Álvaro; Ramírez Boscán, Miguel; Romero Epiayú, Jakeline
Abstract : For more than 30 years after the arrival of the first multinational coal company in La Guajira, the Wayuu have raised their voices. They denounce the extermination of their people, the dispossession of their territory and their resources, and the negligence of the Colombian and Venezuelan states in facing a humanitarian crisis caused by hunger and the death of more than 4, 000 children. The World Health Organization declared the COVID-19 pandemic within this context.